2009
DOI: 10.4067/s0717-95022009000400046
|View full text |Cite
|
Sign up to set email alerts
|

An Unusual Termination of Seven Veins in the Jugulo-Subclavian Junction

Abstract: SUMMARY:During anatomical dissection of a female Caucasian cadaver in our department, we observed an unusual termination of seven veins at the jugulo-subclavian junction. Normally, the jugulo-subclavian junction is formed by the union of the internal jugular vein and the subclavian vein, and gives rise to the brachionocephalic vein. In our case, except from these two, five additional veins, namely the cephalic vein, the transverse cervical vein, the external jugular vein, the anterior jugular vein, and the ver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…Communicating veins may compensate the drainage of veins which are inadequate in size or width as a result of developmental disorders in the region and these veins are usually branches of the common facial vein. [11] Panagouli et al [2] reported that the CV, the TCV, the EJV, the AJV, the IJV and the VV opened to the junction in a clockwise direction on the right side of the neck during cadaver dissection. In our case, it was again clockwise; anteriorly, the common trunk of the EJV and the FV, SCV, the IJV, and posteriorly the SSV combined to form the jugulo-subclavian confluence.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Communicating veins may compensate the drainage of veins which are inadequate in size or width as a result of developmental disorders in the region and these veins are usually branches of the common facial vein. [11] Panagouli et al [2] reported that the CV, the TCV, the EJV, the AJV, the IJV and the VV opened to the junction in a clockwise direction on the right side of the neck during cadaver dissection. In our case, it was again clockwise; anteriorly, the common trunk of the EJV and the FV, SCV, the IJV, and posteriorly the SSV combined to form the jugulo-subclavian confluence.…”
Section: Discussionmentioning
confidence: 99%
“…The anterior connection retracts to form the anteri- The PAV opens to the posterior connection and forms the posterior root of the RMV and drains into the SCV. [2,19] As a result of selective expression or arrest during development in the embryo, abnormal or extra connections between the vessels may occur and cause different images of venous drainage of the region. [6] The connections between the vessels usually occur at the 40 mm stage and sometimes occur early at the 22 mm stage, this situation causes the vessel variations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These superficial veins serve as collaterals and may become prominent in cases of deep venous outflow obstruction. [ 8 ]…”
mentioning
confidence: 99%